2014
DOI: 10.1024/0300-9831/a000196
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin B12 Levels During the First Trimester of Pregnancy Correlate with Newborn Screening Markers of Vitamin B12 Deficiency

Abstract: Newborn screening markers (C3, C3/C2, and C3/C16) present an inverse correlation with maternal vitamin B12 status in the first trimester of pregnancy. Regarding factors that may influence maternal serum vitamin B12 levels during the first trimester, smoking seems to have a negative effect, and meat consumption a positive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Vitamin B 12 deficiency is frequently under-diagnosed in pregnancy and in infants from mothers having insufficient levels of the micronutrient (Wheeler, 2008 ; Sarafoglou et al, 2011 ). Ensuring sufficient intake of vitamin B 12 during pre-conception, pregnancy, and post-partum is strongly recommended (Bjørke Monsen et al, 2001 ; Rasmussen et al, 2001 ; Bjørke-Monsen et al, 2008 ; Hinton et al, 2010 ; Dayaldasani et al, 2014 ). Other populations at risk of developing vitamin B 12 deficiency include the elderly, vegetarians and vegans, recipients of bariatric surgery (Majumder et al, 2013 ; Kwon et al, 2014 ) as well as those suffering from gastrointestinal diseases featuring ileal resections >20 cm (Battat et al, 2014 ).…”
Section: Vitamin B 12 Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin B 12 deficiency is frequently under-diagnosed in pregnancy and in infants from mothers having insufficient levels of the micronutrient (Wheeler, 2008 ; Sarafoglou et al, 2011 ). Ensuring sufficient intake of vitamin B 12 during pre-conception, pregnancy, and post-partum is strongly recommended (Bjørke Monsen et al, 2001 ; Rasmussen et al, 2001 ; Bjørke-Monsen et al, 2008 ; Hinton et al, 2010 ; Dayaldasani et al, 2014 ). Other populations at risk of developing vitamin B 12 deficiency include the elderly, vegetarians and vegans, recipients of bariatric surgery (Majumder et al, 2013 ; Kwon et al, 2014 ) as well as those suffering from gastrointestinal diseases featuring ileal resections >20 cm (Battat et al, 2014 ).…”
Section: Vitamin B 12 Deficiencymentioning
confidence: 99%
“…In addition to the four canonical markers discussed above, vitamin B 12 deficiency leads to accumulation of propionylcarnitine (C3) (Sarafoglou et al, 2011 ), which is a marker of methylmalonic aciduria and propionic acidemia. While vitamin B 12 deficiency is not a primary test in newborn screening programs, a study showed that markers C3, C3/C2, and C3/C16 exhibit a negative correlation with maternal levels of vitamin B 12 in the first trimester of pregnancy, and thus may bear diagnostic value (Dayaldasani et al, 2014 ). Although this finding requires further investigation with respect to the functional biomarkers Hcy and MMA, the finding opens the possibility of early identification of vitamin B 12 insufficiency or deficiency during the first trimester of pregnancy and adequate treatment.…”
Section: Serum Biomarkers Of Vitamin B 12 Deficienmentioning
confidence: 99%
“…Of the remaining 95 papers, 63 were excluded on the basis of the full text. The remaining 32 articles are included in this review, as shown in Supplemental S1 (Adaikalakoteswari et al, ; Ambroszkiewicz, Chelchowska, Lewandowski, Gajewska, & Laskowska‐Klita, ; Baker et al, ; Bakker et al, ; Bergen et al, ; Bodnar et al, ; Coker et al, ; Dayaldasani et al, ; Frery et al, ; D. Furness et al, ; D. L. Furness, Yasin, Dekker, Thompson, & Roberts, ; Gadowsky et al, ; Hay et al, ; Jauniaux, Johns, Gulbis, Spasic‐Boskovic, & Burton, ; Knight et al, ; Knudtson et al, ; Larroque et al, ; Matsuzaki et al, ; McDonald, Perkins, Jodouin, & Walker, ; Mito et al, ; Nilsen et al, ; Ozerol, Ozerol, Gokdeniz, Temel, & Akyol, ; Pagan, Hou, Goldenberg, Cliver, & Tamura, ; Prasodjo et al, ; Relton et al, ; Sram, Binkova, Lnenickova, Solansky, & Dejmek, ; Stark et al, ; Stark, Pawlosky, Sokol, Hannigan, & Salem Jr., ; Van Uitert et al, ; van Wersch, Janssens, & Zandvoort, ; Vandevijvere, Amsalkhir, Van Oyen, & Moreno‐Reyes, ; Yila et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean quality score was 4, and quality scores ranged from 3 to 6. Eleven studies reported lower levels of vitamin B12 in smokers, of which seven were significant (Adaikalakoteswari et al, ; Baker et al, ; Bergen et al, ; Dayaldasani et al, ; Frery et al, ; D. Furness et al, ; Gadowsky et al, ; Hay et al, ; Knight et al, ; McDonald et al, ; Ozerol et al, ; Pagan et al, ; Relton et al, ; van Wersch et al, ) The study assessing smoking using thiocyanate levels found significantly lower levels of vitamin B12 in smoking compared with nonsmoking mothers at two time points in pregnancy (Pagan et al, ). The study assessing the effect of marihuana smoking during pregnancy did not find a correlation with vitamin B12 levels (Knight et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation